The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1532/hsf98.20061166
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pretreatment with Different Topical Vasodilators on Blood Flow in the Internal Mammary Artery: A Prospective Randomized Study

Abstract: Brief treatment of the internal mammary artery with topical vasodilators at normal body temperature significantly increases blood flow in this vessel. The data from this study are particularly valuable in relation to off-pump surgery, in which this vessel is usually anastomosed soon after it is harvested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…However, there has been no de nitive anatomical evidence supporting that perioperative continuous iv application of diltiazem had a direct vasodilatory effect on coronary grafts after the sternum was closed. Diltiazem became the preferred antispasmodic agent because, compared to nitroglycerine, it had more favorable perioperative outcome pro les, including lower incidences of new onset A-b and cardiac ischemia 7,9,21,22 . Noticeably, data from these RCTs also suggest that patients on diltiazem may need prolonged hemodynamic support from inotropic and/or vasoactive support, indicating that the usage of diltiazem may have potential negative perioperative and long-term outcome impacts 22 .…”
Section: Discussionmentioning
confidence: 99%
“…However, there has been no de nitive anatomical evidence supporting that perioperative continuous iv application of diltiazem had a direct vasodilatory effect on coronary grafts after the sternum was closed. Diltiazem became the preferred antispasmodic agent because, compared to nitroglycerine, it had more favorable perioperative outcome pro les, including lower incidences of new onset A-b and cardiac ischemia 7,9,21,22 . Noticeably, data from these RCTs also suggest that patients on diltiazem may need prolonged hemodynamic support from inotropic and/or vasoactive support, indicating that the usage of diltiazem may have potential negative perioperative and long-term outcome impacts 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The literature contains a large number of studies describing the use of papaverine for the indication of intraluminal use for prevention of vasospasm when harvesting and anastomosing arterial and venous grafts. These include a randomized, double-blind, parallel-group comparative study with the medicinal product papaverine in CABG operations [Battaloglu 2007]. One study recommends using papaverine solutions at 37°C to prevent intraoperative spasm [Bilgen 1996].…”
Section: Discussionmentioning
confidence: 99%
“…A previous meta-analysis indicated that perioperative application of different calcium channel blockers (CCBs) had significant outcome benefits for patients undergoing all types of cardiac surgeries requiring cardiopulmonary bypass (CPB)[ 5 ]. Topical application of CCBs on isolated IMAs and RAs consistently showed evidence of vasodilatation and increased blood flow[ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…iloprost[ 13 ]. These investigational drugs were applied in various ways: topically or intra-graft injection[ 6 , 14 ], systemically through bolus and/or intravenous (IV) infusion, or mixed in cardioplegia during CPB[ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%